Solvent retention capacity and swelling index of glutenin in hard red wheat flour as possible indicators of rheological and baking quality characteristics. (May 2020) - Wessels, R.; Wentzel, B.; Labuschagne, M.T.
Abstract: To overcome the cost and expense of milling and baking hundreds of samples in wheat breeding programs, cereal chemists have developed various rapid predictive tests for end-use quality assessment. In this study, five small-scale rapid tests, including Solvent Retention Capacity (SRC) and Swelling Index of Glutenin (SIG), were compared for viability and accuracy to determine end-use quality using small quantities of flour. The tests were applied on commercial hard red spring and hard red winter wheat cultivars from two of the three main production regions in South Africa. Rheological and bread-baking characteristics were related to results of the rapid tests. Highly significant cultivar differences were seen for all rheological and baking-related characteristics, and SRC and SIG parameters, with a strong genotype effect. The environment effect was also highly significant across regions, especially for flour protein content (FPC), which affected the rheological and baking-related characteristics differently across the regions. Correlations among SRC, SIG, rheological, and baking quality-related parameters were highly significant, but inconsistent for the two production regions. Only lactic acid SRC and SIG correlated consistently with the rheological and baking quality-related characteristics in both production regions. Graphical abstract: Image 1 Highlights: Solvent Retention Capacity (SRC) and Swelling Index of Glutenin (SIG) compared. Significant correlations of SRC and SIG with rheological and baking characteristics. Correlations differed for different cultivar sets in two wheat growing regions. Only lactic acid SRC and SIG correlated consistently with flour characteristics.